2014
DOI: 10.3109/10826084.2014.935790
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Alcohol Price and Brand Choice Among Underage Drinkers: Are the Most Popular Alcoholic Brands Consumed by Youth the Cheapest?

Abstract: We examined the influence of price on alcohol brand choice among underage youth. Using a national sample of 1,032 youth ages 13–20, recruited from a national internet panel in 2011–2012, we compared differences in mean prices between popular and unpopular brands; examined the association of price and brand popularity using logistic regression; and rank ordered the average price of top brands. Lower brand-specific prices were significantly associated with higher levels of past 30-day consumption prevalence. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Nonetheless, brand preference is found only among social drinkers. The findings of this study are in line with other quantitative studies which have found that exposure to alcohol advertising not only exerts its effects on drinking behaviours, but also on brand preference [33,34] and brand-specific consumption [35,36] among young people. This study reveals that brand sharing of alcoholic and non-alcoholic beverages could also cause 'spillover effects', from non-alcoholic to alcoholic products or vice versa.…”
Section: Effects Of Brand Advertising and Brand Sharing On Alcohol Usesupporting
confidence: 92%
“…Nonetheless, brand preference is found only among social drinkers. The findings of this study are in line with other quantitative studies which have found that exposure to alcohol advertising not only exerts its effects on drinking behaviours, but also on brand preference [33,34] and brand-specific consumption [35,36] among young people. This study reveals that brand sharing of alcoholic and non-alcoholic beverages could also cause 'spillover effects', from non-alcoholic to alcoholic products or vice versa.…”
Section: Effects Of Brand Advertising and Brand Sharing On Alcohol Usesupporting
confidence: 92%
“…We found a general relationship between lower brand prices and drinking preference among youth, but the brands our survey respondents reported consuming most frequently were not the cheapest available (Albers, DeJong, William, Naimi, Siegel, & Jernigan, 2014). Among the 951 brands for which we obtained both price and youth consumption data, the three most popular brands among underage drinkers were Bud Light beer ($1.60/ounce of alcohol), Smirnoff malt beverages ($2.38/ounce), and Budweiser beer ($1.29/ounce).…”
Section: Resultsmentioning
confidence: 92%
“…While a price cut through sales promotions may shore up consumption in the short term, it may not necessarily determine brand choices in the long run. For example, Albers et al (2014) found that although brands with lower prices had a high-level prevalence of past 30-day consumption, the youth in that study did not necessarily prefer the cheapest brands in the long run. Roberts et al (2016) also reported a similar result because underage drinkers did not consume the cheapest available brands.…”
Section: Brand Preference Among People Who Use Alcoholmentioning
confidence: 82%